Centrifugal fan with inclined blades for vacuum cleaner motor. (November 2018) - Prezelj, Jurij; Novaković, Tadej
Abstract: Centrifugal fans have several technical applications. Their aerodynamic performance is well-optimized nowadays, but the same does not apply to their acoustic performance. Noise control studies of centrifugal fans are often focused on designed operating conditions or operating conditions close to the onset of instability. This paper seeks to find an alternative geometry of the centrifugal fan impeller which would improve noise control of centrifugal fans in a wide range of operating conditions. In this paper, the term noise control refers to noise level reduction and additionally to manipulating the psychoacoustic properties of noise. The experimental work and numerical calculations focus on the centrifugal fan in vacuum cleaners. The experimental work, based on numerical simulations, is described to investigate the influence of the triangular cross section on the flow channel, formed by two inclined blades in opposite directions, on aerodynamic properties and the psychoacoustic performance of the impeller. The study demonstrates that impellers with a triangular flow channel achieve an aerodynamic performance which is comparable to that of standard impellers. The results also show that impellers with inclined blades deliver superior results in psychoacoustic metrics compared to impellers with upright blades.